Image segmentation based on graph theory - Cheevasuvit, F. (My University, 1990)
This paper presents an automatic image classification by segmentation method based on graph theory, where each pixel of an image is mapped onto a vertex of graph and the vertices are connected by the link weights. The segmented regions are obtained by agglomerating the vertices which have minimum link weights under a given homogeneity condition. The result shows the segmented regions are connected and the segmented shapes are independent from the problem of scanning direction.